2003
DOI: 10.1076/clin.17.4.507.27935
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Deficits and Social Functioning in Schizophrenia: A Clinical Perspective

Abstract: Impaired social functioning is one of the diagnostic features of schizophrenia. Cognitive functioning is also often impaired in several domains. Meta-analysis has shown a predictive value of cognition for a variety of domains related to social functioning (Green, Kern, Braff, & Mintz, 2000). The significance of these findings for clinical practice has remained largely uninvestigated, however, and is therefore taken up here. We investigated verbal memory, attention and executive functioning in 52 schizophrenia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Overall, 87% were diagnosed with schizophrenia, 12% with schizoaffective disorder and 1% had other diagnoses in the non-affective psychosis spectrum. Five articles included samples of patients with schizophrenia or schizoaffective disorder but did not report exact numbers (Corrigan and Toomey, 1995;Meyer and Kurtz, 2009;Nakagami et al, 2008;Van Beilen et al, 2003;Velligan et al, 2004). The sample included 76.1% outpatients.…”
Section: Descriptive Informationmentioning
confidence: 99%
“…Overall, 87% were diagnosed with schizophrenia, 12% with schizoaffective disorder and 1% had other diagnoses in the non-affective psychosis spectrum. Five articles included samples of patients with schizophrenia or schizoaffective disorder but did not report exact numbers (Corrigan and Toomey, 1995;Meyer and Kurtz, 2009;Nakagami et al, 2008;Van Beilen et al, 2003;Velligan et al, 2004). The sample included 76.1% outpatients.…”
Section: Descriptive Informationmentioning
confidence: 99%
“…3,4 van Beilen and colleagues concluded that the domains of psychosocial functioning and neuropsychological functioning at the same time point are largely independent of one another. 29 However, it is worth noting that they used self-rated measures of social functioning, which might have influenced their results depending on the insight of the participants. Moreover, all of the above studies relate to persons with chronic schizophrenia, rather than those in the early phases of a psychotic illness.…”
Section: Discussionmentioning
confidence: 99%
“…'s reviews have generally concluded that neurocognitive measures have a stronger relationship with function than negative or positive symptoms, albeit based mainly on correlational studies 3,4 . van Beilen and colleagues concluded that the domains of psychosocial functioning and neuropsychological functioning at the same time point are largely independent of one another 29 . However, it is worth noting that they used self‐rated measures of social functioning, which might have influenced their results depending on the insight of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Although it seems obvious that social cognition could depend and interact with cognitive and community functioning, few attempts towards an integration of theory and findings have been made (van Beilen et al 2003). In this study we attempted to integrate the areas of neurocognition, clinical symptomatology, and community functioning, as well as sociodemographic variables in order to evaluate their ability to predict social reasoning.…”
Section: Discussionmentioning
confidence: 99%